Processing discharge summaries in general practice: a qualitative interview study with GPs and practice managers. Issue 1 (2019) - Spencer, Rachel A; Rodgers, Sarah; Salema, Ndeshi; Campbell, Stephen M; Avery, Anthony J
No abstract available